Influence of row spacing and nitrogen levels on herb and essential oil production and oil quality of Tagetes minuta L. - S Singh, M Yaseen, Man Singh, R S Tripathi, (Journal of Spices and Aromatic Crops, 2008)
The influence of row spacing and levels of nitrogen application on herb and essential oilproduction and quality of oil of South American marigold (Tagetes minuta) was studied atLucknow (Uttar Pradesh). Plant rows spaced at 30 cm distance produced 26% and 69% moreherb and 20% and 47% more oil than 45 cm and 60 cm spacing, respectively. Nitrogenapplication led to linear increase in herb and essential oil production. Application of 150 kgN ha-1 produced maximum oil (71 kg ha -1) which was 142%, 49% and 23% higher, respectivelyover 0, 50 and 100 kg N ha-1. Essential oil biosynthesis was adversely affected in plants thatwere either spaced closer than 60 cm in rows or received higher quantity of nitrogen. Themajor chemical component of oil, dihydrotagetone increased with increase in row spacingand sharply decreased with increase in nitrogen level beyond 50 kg ha-1, while a reversetrend was observed for limonene, (Z)-tagetone and (Z)-tagetenone.